2021
DOI: 10.1111/pce.14138
|View full text |Cite
|
Sign up to set email alerts
|

HSP70‐16 and VDAC3 jointly inhibit seed germination under cold stress in Arabidopsis

Abstract: Abscisic acid (ABA) transport plays a crucial role in seed germination under unfavourable conditions such as cold stress. Both heat shock protein 70 (HSP70) and voltage‐dependent anion channel (VDAC) protein are involved in cold stress responses in Arabidopsis. However, their roles in seed germination with regard to ABA signaling remain unknown. Here we demonstrated that Arabidopsis HSP70‐16 and VDAC3 jointly suppress seed germination under cold stress conditions. At 4°C, both HSP70‐16 and VDAC3 facilitated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 67 publications
(121 reference statements)
1
11
0
Order By: Relevance
“…Recent studies have shown that the heat shock proteins are abundantly expressed under stress conditions such as a high temperature, drought, low temperature, and salt stress [ 24 , 29 , 33 , 34 ]. They maintain plant homeostasis by participating in various biological functions such as protein synthesis, folding, cellular, and cellular localization, and protein degradation [ 6 , 10 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that the heat shock proteins are abundantly expressed under stress conditions such as a high temperature, drought, low temperature, and salt stress [ 24 , 29 , 33 , 34 ]. They maintain plant homeostasis by participating in various biological functions such as protein synthesis, folding, cellular, and cellular localization, and protein degradation [ 6 , 10 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of the corresponding GhHSP24.7 homologous gene in Arabidopsis and tomato promoted a seed germination [ 28 ]. Two genes AtHSP70-16 and AtVDAC3 have been shown to promote an ABA efflux from endosperm to embryo under low-temperature conditions, thereby inhibiting seed germination [ 29 ]. The AtHSP90-mediated AtPIN1 distribution regulates auxin distribution, promoting a development in Arabidopsis [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most grape VaHSP70s showed obvious stress regulation under cold conditions, among which VaHSP70-19 was continuously highly expressed under cold treatment, whereas other VaHSP70s were downregulated ( Liu et al, 2022 ). The levels of Arabidopsis AtHSP70s and the chaperone genes were upregulated after cold treatment, while AtHSP70-16 was negatively regulated in seed germination, which may be a protective mechanism against cold stress ( Ashraf et al, 2021 ). The expression of watermelon ClHSP70-3 , -4 and -5 was upregulated under cold stress, however, ClHSP70-6 and -8 were significantly downregulated at 3 and 6 h ( Figure 8B ).…”
Section: Discussionmentioning
confidence: 99%
“…Arabidopsis AtVDAC1 regulates infection resistance to Agrobacterium tumefaciens . NbVDACs are involved in resistance to Pseudomonas cichorii [ 49 ]. Notably, VDACs also function in Bax-mediated cell death [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%